FACTORS ASSOCIATED WITH FRUIT AND VEGETABLE CONSUMPTION IN A WEST AFRICAN STUDENT POPULATION - SEYDOU MAIGA; Koussoh Simone MALIK; Babou Pascal TIENIN; Julie SACKOU-KOUAKOU (Global Journal of Public Health Medicine)
Introduction: WHO recommends the daily consumption of five servings of fruits and vegetables. The general objective of this study was to identify the factors associated with fruit and vegetable consumption among a population of students in West Africa.